IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DI PROGRAM STUDI PENDIDIKAN BAHASA ARAB UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Sahreebanu, Dhea Syahzana; Nurcholis, Ahmad; Hidayatullah, Syaikhu Ihsan; Rois, Muhammad Nur (STIQ Amuntai, 2022)
This study aims to determine the implementation of the ‘Merdeka Belajar Kampus Merdeka’ (MBKM) curriculum at the Arabic Language Education Study Program of UIN Sayyid Ali Rahmatullah Tulungagung. The Ministry of Education and Culture initiated a new university program, Merdeka Belajar Kampus Merdeka’ (MBKM), to prepare superior and competitive human resources for the 4.0 revolution era. The research method uses field research, which includes qualitative research. Research data was collected from primary and secondary sources, while data collection techniques used documentation, observation, and interviews. This study uses the process of data reduction, data presentation, and conclusion to analyze the data. The findings show that: 1) The strategy of the Arabic Language Education study program of UIN SATU Tulungagung in implementing the MBKM curriculum includes six programs, namely; MBKM Curriculum Review Workshop, National Seminar, MBKM Partner Program, MBKM-based Lecturer Devotion FGD, Department Curriculum FGD Referring to MBKM Policy, and MBKM Curriculum Alignment FGD. 2) Programming of the MBKM-based Arabic Language Education study program of UIN SATU Tulungagung has been carried out in six areas, namely; homeland student exchange (a.k.a. Permata) scheme 512, teaching assistance in education units, student professional practice (a.k.a. PPM), research, entrepreneurial activities, and MDB Community Service Program. 3) Re-curriculum for the Arabic Language Education study program of UIN SATU Tulungagung, which has two optional curricula: regular and MBKM.Keywords: Curriculum, MBKM, Arabic Language Education